2012
DOI: 10.1371/journal.pone.0048141
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Enhances Neurogenesis and Oligodendrogenesis in Ischemic Brain of Middle-Aged Mouse

Abstract: Adult neural stem cells give rise to neurons, oligodendrocytes and astrocytes. Aging reduces neural stem cells. Using an inducible nestin-CreERT2/R26R-yellow fluorescent protein (YFP) mouse, we investigated the effect of Sildenafil, a phosphodiesterase type 5 (PDE5) inhibitor, on nestin lineage neural stem cells and their progeny in the ischemic brain of the middle-aged mouse. We showed that focal cerebral ischemia induced nestin lineage neural stem cells in the subventricular zone (SVZ) of the lateral ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 45 publications
(90 reference statements)
3
73
0
Order By: Relevance
“…69 Using a fate mapping strategy, studies demonstrate that stroke increases neural stem cell lineage OPCs and promotes these OPCs to differentiate into myelin forming oligodendrocytes in peri-infarct white matter. [49][50][51][52][53] These data suggest that OPCs generated by adult neural stem cells contribute to oligodendrogenesis after stroke.…”
Section: Perinatal H/i Injury and Stroke-induced Oligodendrogenesismentioning
confidence: 86%
“…69 Using a fate mapping strategy, studies demonstrate that stroke increases neural stem cell lineage OPCs and promotes these OPCs to differentiate into myelin forming oligodendrocytes in peri-infarct white matter. [49][50][51][52][53] These data suggest that OPCs generated by adult neural stem cells contribute to oligodendrogenesis after stroke.…”
Section: Perinatal H/i Injury and Stroke-induced Oligodendrogenesismentioning
confidence: 86%
“…Mature oligodendrocytes are terminally differentiated and are vulnerable to cerebral ischemia. During brain repair processes, new oligodendrocytes generated by OPCs form myelin sheaths around the regenerated axons in periinfarct gray and white matter (48)(49)(50)(51). Recent studies indicate that cerebral endothelial cells actively and mutually interact with oligodendrocytes to facilitate angiogenesis and oligodendrogenesis during repair after stroke (52).…”
Section: Exosomes and Cerebral Angiogenesismentioning
confidence: 99%
“…For instance, the elevation of cGMP by sildenafil (10 mg/kg) enhances neurogenesis, angiogenesis, and synaptic plasticity, closely associated with improvements in neurological outcome and memory in animal models of adult stroke 30,31 and Alzheimer's disease. 32 Recently, Zhang et al 33 have also demonstrated that sildenafil enhances nestin expression in neural stem cells and the generation of neuronal and oligodendroglial progeny in the ischemic brain of the middle-aged mouse. Whether sildenafil could induce similar changes in the developing brain remains to be elucidated.…”
Section: March 2014mentioning
confidence: 99%